La création des musées d’art contemporain de province en Grèce dans les années 1960 - Christina Ntaflou (Territoire en Mouvement)
The creation of public art galleries in the 20th century in Greece is seen through the lens of different transitions the country went through during the post second world war period. The public of art buyers is almost inexistent and the situation is discouraging for painters. The year 1960 though is perceived as an important historical moment, as the first art gallery is opened in the North-West region of the country, at Ioannina. We can identify in this act the beginnings of the professionalization of the sector of artists and their social status, both connected to an economic dynamism as well. Departing from this period and until the junta regime (1967-1974), cultural effervescence is motivated by artists, educated bourgeois and, often, people of a left-wing ideology. It is also a period of urban, economic and artistic changes all through the country (modernism and development). The importance of a town’s gallery is recognized by people of the Athens’ art world and that adds a symbolic character of importance to the museum and city. The existence of an artistic gallery gives also the possibility to speak of touristic, financial and art market development. Art museums are new institutions for visual arts and, besides proving the evolution of the local (often rural) society, they “define” the map of the city (by their architecture), giving it its new cultural venues. Artists and different associations are holding a very important place in the defense of these museums. Considering that museums function as mirrors for the society, we will examine how these institutions contribute to national discourses, artistic renovation and economic evolutions likewise, through the study of some cases.